2017
DOI: 10.1111/vox.12560
|View full text |Cite
|
Sign up to set email alerts
|

Preceding haemorrhagic shock as a detrimental risk factor for respiratory distress after excessive allogeneic blood transfusion

Abstract: Background and Objectives Whether transfusion-associated circulatory overload arises as a simple result of over-transfusion or requires another trigger remains unclear. Here, we examined whether respiratory distress could be reproduced by massive transfusion alone in an animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…All animals had a positive fluid balance, and with equal amounts of fluids infused, there is a greater increase in pulmonary capillary pressure, heart rate, and blood pressure in the transfusion group. Our results confirm initial findings of increased pulmonary pressures after transfusion reported by Masuda et al Massive volume infusion of otherwise healthy swine, that is, infusion of an additional 100% of ECV, similarly increased pulmonary pressures after whole blood but not LR. The main limitation in the previous study was the use of mean pulmonary artery pressure, instead of left atrial pressure or LVEDP, as this pulmonary artery pressure can be elevated in the absence of circulatory overload.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All animals had a positive fluid balance, and with equal amounts of fluids infused, there is a greater increase in pulmonary capillary pressure, heart rate, and blood pressure in the transfusion group. Our results confirm initial findings of increased pulmonary pressures after transfusion reported by Masuda et al Massive volume infusion of otherwise healthy swine, that is, infusion of an additional 100% of ECV, similarly increased pulmonary pressures after whole blood but not LR. The main limitation in the previous study was the use of mean pulmonary artery pressure, instead of left atrial pressure or LVEDP, as this pulmonary artery pressure can be elevated in the absence of circulatory overload.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the incidence of TACO differs between transfusion products, an effect that cannot be explained solely by the infusion of volume. Previous studies in otherwise healthy animals as well as human volunteers show that even massive and rapid infusion of crystalloids (30 mL/kg at 100 mL/min) does not result in cardiac overload. In line with this, a retrospective study in critically ill patients found that significantly less volume of blood product was required to develop TACO compared to patients with conventional fluid overload …”
mentioning
confidence: 93%
“…Hemorrhagic shock was associated with the highest odds ratio, although this risk factor was only described by Menis et al A large amount of blood component as well as nonsanguineous fluid volume is probably involved, though an inflammatory mechanism may play a role …”
Section: Discussionmentioning
confidence: 93%
“…Other experimental protocols with comparable porcine transfusion models investigate questions like acute kidney injury or effects of blood storing and cooling. Several similar but, in some points, different protocols have been described that make use of autologous instead homologous blood, heavier animals to minimize the need for donor animals, or previously induce a hemorrhagic shock to reduce the rate of circulatory overload (Biagini et al, 2017; Masuda et al, 2018; Patel et al, 2011; Wozniak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the risk of unpredictable removal of the donor blood, hemodynamic variations, and potential microcirculatory or inflammatory impairment during this complex procedure, we decided to decline this option. Small volume withdrawal prior to the transfusion procedure may represent a reasonable compromise, and may reduce the risk of TACO (Masuda et al, 2018). The use of plasma instead of whole blood is an interesting alternative approach to optimize this setting: theoretically, plasma administration will not increase the hemoglobin content, whereas full concentration of potentially inflammatory mediators should be present.…”
Section: Discussionmentioning
confidence: 99%